Application of expert-system for talent scouting in dancing - Srhoj, L.; Mihaljevic, D.; Cavala, M. (Acta Kinesiologica, 2010)
Selection of athletes is most frequently done without any clear criteria, on a low methodological level and by subjective and not scientifically based assessments. Being aware of the importance of taking a correct direction in sports, a new expert system for talent scouting in sport - Talent, has been developed at the Faculty of Kinesiology in Split and the Polytechnics Institute of the Faculty of Natural Sciences and Mathematics in Split, formed in a way to integrate into the existing system of following and evaluating anthropological characteristics of children in primary or secondary schools. Since the existing knowledge base, involving 14 different kinesiological activities, did not involve dance activities, the aim of this research was to determine quantitative contributions of certain motor abilities to the potential dance efficiency through expert knowledge. Good metrical characteristics of the expert knowledge were determined, and after the implementation of the results of research into the system, we established its fine prognostic efficiency in recognizing individuals engaged in dance activities. The obtained results will be used in further improvement of the expert system with the purpose of its more reliable use in the processes of selection and detecting talents in sports.